Coverage of Hiv/Aids in Malaysia: a case study of the star - Tham, Jen Sern; Hasmah Zanuddin (Universiti Kebangsaan Malaysian, 2012)
Living in a globalized world spearheaded by technological advancement and innovations, media have long been instrumental in imparting various kinds of information towards the populace. Consistent with the overwhelming growth of health communication, it is essential to use appropriate media channels to alarm the public on the severity of various diseases. However, it is a challenge for media practitioners to convey such messages in an explicit context. Veiled messages in news reporting of the disease only may result in uncertain, shallow and ambiguous understanding among the readers. On that account, this study seeks to examine the nature and pattern of the news coverage on HIV/AIDS to generate awareness among the people with more care and responsibility. Based on the 72 articles attributed by The Star, only 61 articles fitted the identified themes. The findings indicate that both themes: government response and community involvement on the issue of HIV/AIDS in Malaysia were prominent in the newspaper in year 2006 compared for the year 2011.